Management of Monstrous Fetal Dystocia in a Crossbred Cow - Praveen Kumar, Mudamanasu; Uma Maheswari, Sakunala; Aruna, Yadagiri; Anthony Raju, Kangonu; Mounika, Mendu (The Indian Journal of Animal Reproduction, 2026)
Abnormal joint fixation, or fetal ankylosis, can make it difficult to deliver the calf normally and may require more com plex obstetrical operations, such as fetotomy or cesarean surgery. The current case report details the incidence of dystocia in a crossbred cow brought on by forelimb ankylosis and schistosomus reflexus that was effectively treated by performing fetotomy.